Municipal hymns as expressions of social dreams and aspirations - Puguon, Karen A. (Research Journal in Advanced Humanities, 2023)
Music is the food of the human soul. As a more rhythmic kind of poetry, music helps to capture and express the complex experiences of human life and reality. Municipal hymns are a type of music with a didactic purpose; they seek to promote the collective knowledge and moral uprightness in society. Yet, there is a dearth of scholarship on how such songs reflect the dreams and aspirations of their source communities. Therefore, this study analysed municipal hymns to determine how they express social dreams and aspirations of the Ifugao people. The study was conducted in the province of Ifugao in the Philippines. In particular, the Local Government Units were involved especially in obtaining the official local/municipal hymns. The study was qualitative and adopted an analytical design. The research further deployed structuralism and textual analysis for data collection and analysis. The findings of the study revealed that the hymns capture the dreams and aspirations of the Ifugao people. Through the hymns, the Ifugao express nostalgia for the good times of their history. They also express their desire for a morally upright society. The hymns further capture the aspiration for national values. The study provides a framework for interpreting municipal hymns and similar music to understand the collective value they have in society.